Development of Fluorescence-Based Method for Dopamine Determination Using o-Phthaldialdehyde and 3-Mercaptopropyltriethoxysilane - Valeriia Sliesarenko; Marijana Krstić; Urban Bren; Aleksandra Lobnik (Sensors)
Nanomaterials and sensors play an important role in modern technologies, including medical diagnostics and biochemical research. This work presents the possibility of using o-Phthaldialdehyde (OPA) in combination with 3-mercaptopropyltriethoxysilane (MPTES) to develop a dopamine-responsive sensor. During the experiment, these materials were used at different pH and ratios to determine the optimal parameters for obtaining high fluorescence intensity of the reaction product. The data obtained demonstrate a linear relationship between the fluorescence response (λex/λem = 340/460 nm) of OPA/MPTES and dopamine concentration in the range of 0.1–3.0 µM at a pH of 8, and the detection limit was 8.7 nM. The obtained results confirm the potential of OPA/MPTES as a sensing component for the detection of dopamine.